Tinjauan Pustaka Sistematis : Strategi Digital Marketing - Novendra, Rizki; Turnandes, Yogo; Vebby, Vebby; Nugroho, Gilang; Ohara, Muammar Revnu; Manahan, Marcelius Raja (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research conducted systematic literature observations on digital marketing strategies using the PRISMA diagram protocol to filter articles from the Scopus database. Research methods include data extraction, initial data collection, data inclusion, and answering research questions. Of the 200 articles registered in Scopus, 91 articles were selected for review. This research has three main questions: how is the evolution of digital marketing strategies, what is the impact, and what technologies or tools are used.The results show that the evolution of digital marketing strategies starts from the Web 1.0 to Web 4.0 Era, characterized by the internet, search engines, social media, mobile marketing, big data and analytics, as well as (AI) and machine learning. Digital marketing strategies have a significant impact on business decision making, improved performance, and reach through influencers. The most frequently used tools are SEO (15%), email marketing (20%), Google Analytics (34%), AI (21%), IoT (2%), and big data (8%).